Pengembangan Miniatur Konversi Energi Gerak Sebagai Media Pembelajaran Fisika Kontekstual - Nuril Husna; Muhammad Yakob; Dona Mustika (Jurnal Pendidikan Fisika dan Sains, 2019)
This study aims to determine the miniature of the conversion of motion energy can be used as a medium for contextual physics learning. This type of research is development research using the R & D (Research and Development) method which adopts the development of Gravermaijer and Cobb. The population in this study were all class X in SMA Negeri 4 Langsa and the sample in this study was class X MIPA 1 with a total of 22 students. The results of this study are miniatures of the conversion of motion energy into electrical energy. The value of media validation gained 99% and material validation was 82.5%. Based on the validation values, the developed media is declared suitable for use as a contextual physics learning media for energy conversion material. The results of student responses also showed that learning physics using miniature energy conversion was "very interesting" for students with an average response rate of 85.4%. Suggestions in this research are Miniature energy conversion which is developed is the conversion of motion energy into electricity. for further development it is recommended to be able to develop other types of energy conversion. Keywords : Development, Miniature, and Learning Media